Forecasting Exports across Europe: What Are the Superior Survey Indicators? - Robert Lehmann (Center for Economic Studies and ifo Institute (CESifo), 2019)
In this study, we systematically evaluate the potential of a bunch of survey-based indicators from different economic branches to forecasting export growth across a multitude of European countries. Our pseudo out-of-sample analyses reveal that the best-performing indicators beat a well-specified benchmark model in terms of forecast accuracy. It turns out that four indicators are superior: the Export Climate, the Production Expectations of domestic manufacturing firms, the Industrial Confidence Indicator, and the Economic Sentiment Indicator. Two robustness checks confirm these results. As exports are highly volatile and turn out to be a large demand-side component of gross domestic product, our results can be used by applied forecasters in order to choose the best-performing indicators and thus increasing the accuracy of export forecasts.
Keywords: F01; F10; F17; 330; export forecasting; export expectations; export climate; Europe